Effect of Fluid Viscosity on Earthquake Nucleation. Issue 12 (15th June 2020) - Cornelio, C.; Violay, M.
Abstract: Injection of fluids in geo‐reservoirs can reduce the effective stresses at depth, lubricating the nearby faults, promoting slip and, potentially, earthquakes. High‐viscous fluids are often used during hydraulic fracturing and production phases in geo‐reservoirs. Here, we performed dedicated experiments to study the influence of fluid viscosity on earthquake nucleation. We performed frictional sliding experiments at 30 and 50 effective normal stresses and fluids viscosity ranging from 1 to 1, 226 mPa s and modeled them with a rate‐and‐state friction law. In the presence of fluid, the state variable is defined as the ability of the fluid to flow. Our results showed that static friction slightly decreases with increasing viscosity, the dynamic friction is governed by the dimensionless Sommerfeld number ( S  = 6 ηVL /( σ ' n H 2 )). Moreover, we observed that the ( a  −  b ) parameters of the rate‐and‐state friction law decrease with increasing viscosity down to ( a  −  b ) < 0, possibly promoting unstable slip and earthquake nucleation. Plain Language Summary: In the last 30 years, the exponential worldwide increase of human‐induced seismicity has become an important issue in solid earth sciences. Most of the induced seismicity is due to engineering operations in deep geo‐reservoirs for hydrocarbon production, CO2 storage, wastewater disposal, and the exploitation of geothermal resources. While the reactivation of faults at the origin of this seismicity has been extensively studied, the influence of fluid properties including its viscosity has been overlooked, even if the viscosity of injected fluids spans from that of water to that of honey. In this study, we discuss the influence of fluid viscosity on the nucleation of earthquakes in fluid‐permeated experimental faults and on induced earthquakes. Our experimental observations suggest that the viscosity of the fluid does not influence the fault strength. Instead, the viscosity of the fluid controls the behavior of the fault from stable to unstable sliding. Key Points: We performed velocity‐step experiments in the presence of fluids with different viscosities In the presence of viscous fluid on the slip plane, the state variable of rate‐and‐state frictional laws represents the state of the fluid ( a  −  b ) rate‐and‐state frictional parameters depend on effective normal stress and fluid viscosity